High Perforin‐Positive Cardiac Cell Infiltration and Male Sex Predict Adverse Long‐Term Mortality in Patients With Inflammatory Cardiomyopathy. Issue 8 (18th August 2017) - Escher, Felicitas; Kühl, Uwe; Lassner, Dirk; Stroux, Andrea; Gross, Ulrich; Westermann, Dirk; Pieske, Burkert; Poller, Wolfgang; Schultheiss, Heinz‐Peter
Abstract : Background: The authors analyzed the effects of perforin‐dependent infiltration on long‐term mortality in patients with inflammatory cardiomyopathy (CMi). We previously demonstrated that left ventricular function deteriorates and progresses to substantial cardiac dysfunction in patients with perforin‐positive cardiac cell infiltration. Methods and Results: Between 2003 and 2013, 2389 consecutive patients with clinically suspected CMi who underwent endomyocardial biopsies were enrolled. Endomyocardial biopsies were performed at first admission after exclusion of ischemic or valvular heart disease, and CMi was confirmed in 1717 patients. Follow‐up was up to 10.1 years (median 0.47 years; interquartile range, 0.03–2.56 years) and information on vital status was obtained from official resident data files. Multivariable statistical analysis was conducted for all patients with CMi regarding significant predictors of all‐cause mortality or need for heart transplantation. Multiple Cox regression analysis revealed perforin above the calculated cutoff point of 2.9 cells/mm² as a strong predictor of impaired survival with a hazard ratio of 1.881 (95% confidence interval, 1.177–3.008; P =0.008), independent of left ventricular function and other myocardial inflammation markers (CD3, macrophage‐1 antigen, leukocyte function–associated antigen‐1, human leukocyte antigen‐1, and intercellular cell adhesion molecule‐1). Unexpectedly, male sex emerged as another strong adverse predictor of survival in CMi (hazard ratio, 1.863; confidence interval, 1.096–3.168 [ P =0.022]). Whereas left ventricular ejection fraction course is adversely affected by myocardial perforin, multivariate analysis indicates that left ventricular ejection fraction explains only part of the observed overall mortality. Conclusions: High perforin‐positive cardiac cell infiltration and male sex are independent adverse predictors of long‐term mortality in CMi. Furthermore, exact quantification of immunohistochemically detected infiltrates is necessary to assess the prognosis.